Optimized expression of capsid protein from red-grouper necrosis virus displayed on Pichia pastoris in shake flasks - Chutoam, Palatip; Sirinipatkul, Piyapong; Senabunyarith, Apinan; Eakpanit, Thipakorn; Yamee, Pattamawan; Intamaso, Uraiwan (Agriculture and Natural Resources, 2023)
Importance of the work: High antigen levels on the yeast cell surface are critical in designing oral vaccines against viruses. Objectives: To investigate the environmental factors affecting the production of RNA2/AGα-1, a displayed fusion protein. Materials & Methods: The recombinant Pichia pastoris was cultivated in shake-flask culture under varying conditions and induced with methanol for 168 hr. Total cell proteins were used as a measure of cell population growth. The expression of the RNA2 fusion protein was also characterized by western blot, immunofluorescence and enzyme-linked immunosorbent assay (ELISA). Results: The recombinant P. pastoris (Muts) strain produced optimal growth and product yields using 72 hr post-induction and 0.5% methanol. Prior to induction, the yeast relied on glycerol as the sole carbon source to increase biomass under favorable conditions: 23 °C in an Erlenmeyer flask (5 L) containing 1 L buffered minimal glycerol complex medium (pH 6.0) with vigorous shaking (300 revolutions per minute). Using these optimal conditions, western blot analysis revealed that the RNA2 fusion protein had a molecular weight of approximately 73 kDa. These proteins were localized on the yeast cell surface, as proven based on immunofluorescence labeling at a minimum of 1,000 ng and measured using ELISA. Main finding: The method developed successfully increased the expression of capsid proteins from the virus on the yeast cell surface in a shake flask culture. Large-scale production is required before investigating the potential use of the fusion protein as an oral vaccine in fish.